Online Based Baitul Mal Wat Tamwil (BMT) Management Training In Gampong Panggoi: Pelatihan Pengelolaan Baitul Mal Wat Tamwil (BMT) Berbasis Online Di Gampong Panggoi - Faisal, Faisal; Raihan Putri; Tasyukur; Fitria Mardhatillah; Tunnur, Layla Tunnur; Diras (Universitas Lancang Kuning, 2024)
BMT services that are still manual cause customers difficulties in transactions, information services and consultations as a result of ineffective services. The development of BMT has succeeded in becoming a reliable microfinance institution, expected to be a substitute for loan sharking practices that are considered detrimental to MSMEs in prolonged debt. The problem in this service is that BMT services are still manual, causing customers difficulty to transact and the lack of information obtained. The service method carried out is training which aims to provide training to Gampong apparatus and Gampong Panggoi BMT administrators in terms of online-based BMT management to make it easier to transact and get wide information. As a result of this training, Gampong Panggoi has been able to manage BMT Babul Huda Panggoi online. This online management has been able to run information systems and services using technology by not ruling out sharia aspects and safeguarding customer data and applying the precautionary principle.